News Notes. - Hendriksen, Eldon S. (The Accounting Review, 1971)
Abstract The article presents information related to the department of accounting in various universities in the U.S. In the University of Arizona, Jim G. Ashburne of the University of Texas at Austin is a visiting professor for the Spring Semester 1971. Edwin A. Bump, who completed doctoral work at the University of Missouri, joined the faculty as an assistant professor in September 1970. Taylor W. Foster, who is completing doctoral work at Pennsylvania State University, will join the faculty as an Assistant Professor in September 1971. At the California State College at Fullerton, new faculty for the academic year 1970-71 include Robert W. Vanasse, professor of accounting, previously on the faculty of Ohio State University; Donald J. Barnett and John F. Williams, assistant professors. Robert A. Meier, Chairman, represented the Department at the Faculty Seminar in Palo Alto sponsored by the California Certified Public Accountants Foundation for Education & Research in August 1970. At the DePaul University, Helene Ramanauskas has taken a leave of absence to study quantitative methods at the University of Georgia.